Analysis of Stunting in Indonesia 2021-2023: Impacts and Challenges - Hilda Nur Andini; Siti Fatimah Nurhayati (Universitas Muhammadiyah Surakarta, 2025)
Purpose: This study examines the impact of socioeconomic factors on stunting prevalence in Indonesia from 2021–2023. Using panel data regression with a Random Effect Model (REM) across 34 provinces, four independent variables were analyzed: poverty rate, unemployment rate, GRDP per capita, and number of health workers. Results show that poverty positively and significantly affects stunting, while GRDP per capita has a significant negative effect. Meanwhile, unemployment and health worker variables are insignificant. The R² value of 0.2877 indicates that 28.77% of stunting variation is explained by the model, with the rest influenced by external factors. The findings highlight that economic improvement and poverty reduction are key strategies to lower stunting prevalence in Indonesia.